Buffalo hunting: from a commodity to a high-value game species - (:unkn) unknown (My University, 2023)
Whether practiced legally or illegally, formally or informally, hunting buffalo for meat occurs broadly across African cultures. Nearly all buffalo parts are prized in addition to the meat. Buffalo are also hunted for traditional medicine, social positioning, mystical reasons and in retaliation for causing damage to people and crops. The buffalo is a major game for the hunting industry in every country, but the reasons vary from place to place. In South Africa, buffalo is the first income-generating game despite being the least hunted of all important game. In Tanzania, despite a trophy fee that is lower than that of other species, buffalo is the top tax-earning game because it is the most hunted among the important game. As duly gazetted protected areas, hunting areas are contributing internationally to the global network of conservation areas. They more than double the land area that is used for wildlife conservation in sub-Saharan Africa. Acting as buffer zones of national parks and as corridors between national parks, hunting areas are the last frontier of the African buffalo outside national parks. In South Africa, where all buffalo are fenced and buffalo hunting occurs behind fences, the buffalo is subject to genetic manipulation to enlarge trophy horns and produce disease-free herds. While 'clean buffalo' widely contributed to expanding the land dedicated to wildlife conservation in a beef-exporting country, 'augmented buffalo' remain a matter of concern for the long-term conservation of the taxon. Several non-African countries imposed bans on importing hunting trophies of CITES-listed species from Africa, leading to a drop in the hunting market. The bans are having two impacts on buffalo: (i) although not CITES-listed, the buffalo is a collateral victim of the bans because many abandoned hunting areas are exposed to poaching and habitat conversion; and (ii) unintentionally, the bans are lifting the value of buffalo as a leading flagship game in
Keywords: African Research